Synaptic Plasticity and Neurological Disorders in Neurotropic Viral Infections - Venkata Subba Rao Atluri; Melissa Hidalgo; Thangavel Samikkannu; Kesava Rao Venkata Kurapati; Madhavan Nair (Neural Plasticity)
Based on the type of cells or tissues they tend to harbor or attack, many of the viruses are characterized. But, in case of neurotropic viruses, it is not possible to classify them based on their tropism because many of them are not primarily neurotropic. While rabies and poliovirus are considered as strictly neurotropic, other neurotropic viruses involve nervous tissue only secondarily. Since the AIDS pandemic, the interest in neurotropic viral infections has become essential for all clinical neurologists. Although these neurotropic viruses are able to be harbored in or infect the nervous system, not all the neurotropic viruses have been reported to cause disrupted synaptic plasticity and impaired cognitive functions. In this review, we have discussed the neurotropic viruses, which play a major role in altered synaptic plasticity and neurological disorders.